The rise of the network: the case of our Walmart - Wood, A (British Universities Industrial Relations Association (BUIRA), 2014)
Despite the fact that private-sector unionisation in the United States has reached a historic low, 2012 saw Walmart's first ever nationwide strike. This strike was not carried out by a union and the aim was not collective bargaining. Strikes and other collective acts sought to leverage ideological power, in order to cause symbolic, rather than economic damage. Mass self-communication networks, such as Facebook, connected geographically dispersed actions, transforming them into interconnected collective acts. This article elaborates on Castells' pioneering research by demonstrating that mass self-communication networks can enable the labour movement to adopt new organisational forms and repertoires of action that go beyond restrictive labour laws. These findings are drawn from six weeks of intensive participant observation of Californian Walmart workers' attempts at mobilisation, combined with 42 semi-structured interviews with 33 workers and union officials, and supplemented by an indicative media content analysis.